Cosmopolitan bioethics under pressure: reflections on the Global Observatory for Genome Editing International Summit - Schütz, Nils (The CRISPR journal, 2025)
This article reflects reflection on the Fourth International Summit on Genome Editing, organized by the Global Observatory for Genome Editing. It examines current challenges to the Observatory's project of advancing "cosmopolitan bioethics" that are inclusive, interdisciplinary, and sensitive to diverse understandings of what it means to be human. Focusing on tensions between scientific urgency and ethical deliberation, this article addresses the limitations of the Observatory's "anthropology-first" approach, the symbolic framing of genome editing as a "wicked problem," and the epistemic and geopolitical asymmetries that continue to shape global bioethics. I argue for honest engagement with competing moral convictions, practical needs, and global inequalities in order to preserve and deepen the promise of cosmopolitan bioethics.